The loss‐of‐function mutations and down‐regulated expression of ASB3 gene promote the growth and metastasis of colorectal cancer cells. Issue 1 (14th January 2017) - Du, Wu‐Ying; Lu, Zhen‐Hai; Ye, Wen; Fu, Xiang; Zhou, Yi; Kuang, Chun‐Mei; Wu, Jiang‐Xue; Pan, Zhi‐Zhong; Chen, Shuai; Liu, Ran‐Yi; Huang, Wen‐Lin
Abstract: Background: Ankyrin repeat and SOCS box protein 3 (ASB3) is a member of ASB family and contains ankyrin repeat sequence and SOCS box domain. Previous studies indicated that it mediates the ubiquitination and degradation of tumor necrosis factor receptor 2 and is likely involved in inflammatory responses. However, its effects on oncogenesis are unclear. This study aimed to investigate the effects of ASB3 on the growth and metastasis of colorectal cancer (CRC). Methods: We used next‐generation sequencing or Sanger sequencing to detect ASB3 mutations in CRC specimens or cell lines, and used real‐time quantitative polymerase chain reaction, Western blotting, and immunohistochemical or immunofluorescence assay to determine gene expression. We evaluated cell proliferation by MTT and colony formation assays, tested cell cycle distribution by flow cytometry, and assessed cell migration and invasion by transwell and wound healing assays. We also performed nude mouse experiments to evaluate tumorigenicity and hepatic metastasis potential of tumor cells. Results: We found that ASB3 gene was frequently mutated (5.3%) and down‐regulated (70.4%) in CRC cases. Knockdown of endogenous ASB3 expression promoted CRC cell proliferation, migration, and invasion in vitro and facilitated tumorigenicity and hepatic metastasis in vivo. Conversely, the ectopic overexpression of wild‐type ASB3, but not that of ASB3 mutants that occurred in clinical CRC tissues, inhibited tumor growth and metastasis. Further analysis showed that ASB3 inhibited CRC metastasis likely by retarding epithelial‐mesenchymal transition, which was characterized by the up‐regulation of β‐catenin and E‐cadherin and the down‐regulation of transcription factor 8, N‐cadherin, and vimentin. Conclusion: ASB3 dysfunction resulted from gene mutations or down‐regulated expression frequently exists in CRC and likely plays a key role in the pathogenesis and progression of CRC.